2012
DOI: 10.1017/jrc.2012.4
|View full text |Cite
|
Sign up to set email alerts
|

Personal Factors in the International Classification of Functioning, Disability and Health: Prospective Evidence

Abstract: The goal of this study was to propose a systematic classification of relevant personal factors for describing the background of an individual's life and way of living. The German Society of Social Medicine and Prevention constituted an ICF working group consisting of members from Medical Advisory Boards of Statutory Health Insurances (n = 6) and other institutions (n = 12) in 2009. A two-tier consensus building approach was utilised to construct and document the personal factors, with an initial team of expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 12 publications
2
52
0
3
Order By: Relevance
“…The participants' socio-demographic background was summarized using descriptive statistics. Personal factors were linked to second-level categories as classified by Grotkamp et al [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants' socio-demographic background was summarized using descriptive statistics. Personal factors were linked to second-level categories as classified by Grotkamp et al [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been attempts to classify personal factors into categorical codes. For example, Grotkamp et al [26] proposed to structure 72 personal factors into 6 different chapters. The ICF-CY, which includes all ICF-categories, plus additional ones for children and youth, consists of 1685 categories (531 body functions; 329 body structures; 552 activities and participation categories; and 273 environmental factors).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the development of the ICF component ''personal factors'' seems to be basic for a stringent ICF-based description of rehabilitation interventions [27]. After the recent publication of a suggested classification of personal factors [78], future discussion will show its acceptance in rehabilitation science and its usefulness for describing complex interventions which target behaviour change.…”
Section: Discussionmentioning
confidence: 99%
“…This model comprises the components "Activities and participation", "Personal factors", "Environmental factors", and "Body Functions and Body structures". 5,9,10 The model included pain as an impairment (body function), and personal factors as possible mediators for participation in valued activities. Previous research has demonstrated associations between management strategies and participation in valued activities.…”
Section: Methodsmentioning
confidence: 99%